Implementasi Metode NWC (North West Corner) Untuk Menentukan Alokasi Waktu Optimal Dalam Penggunaan Aplikasi DJP (Direktorat Jenderal Pajak) Online - Taslima Dewi; Hanifa Mardiatun Nasution; Nur Manda Sari; Rina Filia Sari; Elis Citra Purnama Purba; Shopia (Unity Academy, 2023)
Practical Work (KP) is a direct job training program that is implemented from higher education institutions to students in the work environment, which aims to improve skills and provide experience to students. The problem that occurs at the KP is the lack of BKKBN employees in managing time to upload data in the DJP online application. Therefore, the practitioner tries to use the NWC (North West Corner) method to optimize the time for uploading data in the DJP online application. By using the NWC (North West Corner) method, the optimal time allocation needed for BKKBN employees to upload data in the DJP online application is to make it more efficient, namely 3.72 hours/day.